Overvoltage protection for grid-connected picohydro generation using photovoltaic inverters - Scotta, Isabella Cristina (2022)
Very small-scale hydropower plants are environmentally friendly and renewable resource-based innovative solutions. The interest in pico-hydro systems (up to 5 kW) has increased significantly from the first stand-alone applications, at remote sites, to the distributed generation, with the injection of generated energy into the grid. Recently, there have been advances in the grid connection of these systems using off-the-shelf components, namely photovoltaic inverters. Therefore, pico-hydro systems have gained an enormous potential in distributed generation, particularly in the context of microgrids. However, in situations of over-power, or whenever the generator is under no load, e.g. when the grid fails, there is a need for effective over-voltage protection, as in small wind turbines. This paper proposes two over-voltage protection circuits, designed to ensure the integration of pico-hydro turbines connected to the grid using conventional photovoltaic microinverters and string inverters, for power ranges of 300 W and some kW, respectively. Extensive tests were performed on an emulation platform and a workbench using these two different over-voltage protection circuits. One is designed to connect the generators of water wheels to the grid and the other to connect 1,500 W generators of water turbines. The experimental results demonstrated the performance of the proposed over-voltage protection circuits in four different situations. Both avoid irreversible damages of generators, photovoltaic microinverters and string inverters in the context of the above-described grid connection approach.